An empirical study of long-term personal project information management. Issue 4 (18th July 2016) - Copic Pucihar, Klen; Kljun, Matjaž; Mariani, John; Dix, Alan John
Abstract : Purpose: – Personal projects are any kind of projects whose management is left to an individual untrained in project management and is greatly influenced by this individual's personal touch. This includes the majority of knowledge workers who daily manage information relating to several personal projects. The authors have conducted an in-depth qualitative investigation on information management of such projects and the tacit knowledge behind its processes that cannot be found in the organisational structures of current personal information management (PIM) tools (file managers, e-mail clients, web browsers). The purpose of this paper is to reveal and understand project information management practices in details and provide guidelines for personal project management tools. Design/methodology/approach: – Semi-structured interviews similar to that in several other PIM exploratory studies were carried out focusing on project fragmentation, information overlap and project context recreation. In addition, the authors enhanced interviews with sketching approach not yet used to study PIM. Sketches were used for articulating things that were not easily expressed through words, they represented a time stamp of a project context in the projects' lifetime, uncovered additional tacit knowledge behind project information management not mentioned during the interviews, and were also used to find what they have in common which might be used in prototype designing. Findings: – The paper presents first personal project definition based on the conceptualisations derived from the study. The study revealed that the extensive information fragmentation in the file hierarchy (due to different organisational needs and ease of information access) poses a significant challenge to context recreation besides cross-tool fragmentation so far described in the literature. The study also reveals the division of project information into core and support and emphasises the importance of support information in relation to project goals. Other findings uncover the division of input/output information, project overlaps through information reuse, storytelling and visualising information relations, which could help with user modelling and enhancing project context recreation. Research limitations/implications: – On of the limitations is the group of participants that cannot represent the ideally generalised knowledge worker as there are many different kinds of knowledge workers and they all have different information needs besides different management practices. However, participants of variety of different backgrounds were observed and the authors converged observations into points of project information management similarities across the spectrum of different professions. Nevertheless, its observations and conceptualisations should be repeatable. For one, some of the issues that emerged during this work have been to different extents discussed in other studies. Practical implications: – The empirical findings are used to create guidelines for designing personal project information management tools: support the selective focus on information with the division into core and supportive information; visualise changes in project information space to support narratives for context recreation; overcome fragmentation in the file system with selective unification; visualising project's information relationship to better understand the complexity of project information space; and support navigating in project information space on two axes: time and between projects (overlaps through information). Originality/value: – The study presents a longitudinal insight into personal project information management. As such it provides a first formal definition of personal project from the information point of view. The method used in the study presented uses a new approach – sketching in which participants externalised and visualised personal information and projects they discussed. The insights derived from the study form design implications for personal project management tools for knowledge workers.